PENGARUH KEPUASAN KERJA TERHADAP PERILAKU MENYIMPANG DAN ORGANIZATIONAL CITIZENSHIPBEHAVIOR (Studi pada Baitul Maal wat Tamwi (BMT) di Provinsi Jawa Timur) - Arfah (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2015)
This study is designed to examine the influence of job satisfaction on deviant behavior and Organizational Citizenship Behaviors.This research analyzed the relationship among the variables so that it belongs to explanatory research. It was conducted in 6 institutions of Baitul Maal wat Tamwil (BMT) with 33 branch offices in East Java. The population was 202 employees which 134 of them were taken for the sample of this study. The sample taken was clustered random sampling. The statistic method used to test the hypothesis is regression analysis.The result of this research proves that job satisfaction has significantly negative influences deviant behavior, job satisfaction has significantly positive influences Organizational Citizenship Behaviors, and deviant behavior has not significantly influences Organizational Citizenship Behaviors.